Novel Gene Mutation Variant in Hypomyelinating Leukodystrophy-8: A Case Report - Shalesh Rohatgi; Pranit Khandait; Satish Nirhale; Prajwal Rao; Pravin Naphade (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
The incidence of hypomyelinating leukodystrophies is approximately 1 in every 250,000–500,000 individuals in the population. Hypomyelinating leukodystrophy-8 (HLD-8) is characterized by classical clinical features, including modest intellectual deficits and early-onset progressive cerebellar ataxia, with or without oligodontia and/or hypogonadotropic hypogonadism. In this case report, we present a 34-year-old male who experienced gradually progressive behavioral and memory disturbances over the past 10 years, accompanied by imbalance while walking and complex partial seizures. The patient also exhibited oligodontia and moderate intellectual disability (IQ score: 45). Spasticity was observed in the lower limbs, with exaggerated deep tendon reflexes in all four limbs, and bilaterally extensor plantar responses were noted. Sensory examination results were within normal limits. Bilateral cerebellar signs were present, including gaze-evoked nystagmus in all directions, which was non-fatigable. MRI brain revealed generalized cerebral and cerebellar atrophy, as well as diffuse hyperintensities in T2-weighted images (T2W) and fluid-attenuated inversion recovery (FLAIR) in the bilateral cerebral white matter, with no basal ganglia involvement. The sagittal T1-weighted image (T1W) showed diffuse thinning of the corpus callosum. Whole-exome sequencing revealed a novel variant mutation of the POLR3B gene in HLD-8, specifically in Exon 20 [c.2125A>G (p.Met709Val)] and Exon 23 [c.2699G>A (p.Arg900His)]. Very few case reports and variant mutations on the POLR3B gene on chromosome 12q23.3 have been reported thus far.